2017
DOI: 10.1002/chem.201604395
|View full text |Cite
|
Sign up to set email alerts
|

MoS2/Carbon Nanotube Core–Shell Nanocomposites for Enhanced Nonlinear Optical Performance

Abstract: Nanocomposites of layered MoS and multi-walled carbon nanotubes (CNTs) with core-shell structure were prepared by a simple solvothermal method. The formation of MoS nanosheets on the surface of coaxial CNTs has been confirmed by scanning electron microscopy, transmission electron microscopy, absorption spectrum, Raman spectroscopy, and X-ray photoelectron spectroscopy. Enhanced third-order nonlinear optical performances were observed for both femtosecond and nanosecond laser pulses over a broad wavelength rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…The NLO property of heterostructures based on 2D layered materials is very significant for the nonlinear photonic devices such as optical switch, [14] mode locking laser, [15] optical limiter, [16] and logical circuit. [19] We reported that the nonlinear absorption coefficient of MoS 2 /graphene film is ≈−1217.8 cm GW −1 , which is larger than that of MoS 2 film (≈−136.1 cm GW −1 ) and graphene film (≈−961.6 cm GW −1 ) at the same condition. Li et al reported the nonlinear absorption coefficient (α NL ) of graphene/WS 2 heterostructure (9.7 × 10 4 cm GW −1 ), which is much higher than that of WS 2 (1.33 × 10 3 cm GW −1 ).…”
Section: Introductionmentioning
confidence: 77%
“…The NLO property of heterostructures based on 2D layered materials is very significant for the nonlinear photonic devices such as optical switch, [14] mode locking laser, [15] optical limiter, [16] and logical circuit. [19] We reported that the nonlinear absorption coefficient of MoS 2 /graphene film is ≈−1217.8 cm GW −1 , which is larger than that of MoS 2 film (≈−136.1 cm GW −1 ) and graphene film (≈−961.6 cm GW −1 ) at the same condition. Li et al reported the nonlinear absorption coefficient (α NL ) of graphene/WS 2 heterostructure (9.7 × 10 4 cm GW −1 ), which is much higher than that of WS 2 (1.33 × 10 3 cm GW −1 ).…”
Section: Introductionmentioning
confidence: 77%
“…It is worth noting that the linear absorption and thickness of the as-prepared heterostructure (∼2.23 nm), WS 2 (0.8 nm), and graphene (0.4 nm) also have been taken into account in the calculation by employing the UV-Vis spectrophotometer and atomic force microscopy, in which the graphene∕WS 2 heterostructure exhibited an enhanced linear absorption. By fitting the Z -scan data using the nonlinear absorption model [44,45], the heterostructure exhibited stronger nonlinear optical response with the combination of saturable absorption and multiphoton absorption. The fitted saturable intensity of graphene∕WS 2 heterostructure was 4.72 GW∕cm 2 and the nonlinear absorption coefficient (β) is measured to be 9.7 × 10 4 cm∕GW, which is much higher than 1.33 × 10 3 cm∕GW of WS 2 , which is within a reasonable range under the same condition [43].…”
Section: Experimental Details and Discussionmentioning
confidence: 99%
“…[16,17] However,t he application of MoS 2 anodes suffers from several problems: 1) poor rate capability arising from its low electrical conductivity;2 )rapid capacity decay due to pulverization and restacking of MoS 2 nanosheets;3 )unsatisfactory cycling life owing to the shuttlee ffect of polysulfides and loss of active materials during charge/discharge. Construction of nanostructured MoS 2 materials, such as nanosheets, [20] nanofibers, [21,22] microflowers, [23] and nanospheres, [24,25] is considered to be an effective approach for facilitating the fast transfer of ions and thus enhancing the electrochemical performance. Construction of nanostructured MoS 2 materials, such as nanosheets, [20] nanofibers, [21,22] microflowers, [23] and nanospheres, [24,25] is considered to be an effective approach for facilitating the fast transfer of ions and thus enhancing the electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Therefore, novel strategies for developing advanced MoS 2based anode materials are highly desirable. Construction of nanostructured MoS 2 materials, such as nanosheets, [20] nanofibers, [21,22] microflowers, [23] and nanospheres, [24,25] is considered to be an effective approach for facilitating the fast transfer of ions and thus enhancing the electrochemical performance. On the other hand, combining MoS 2 with conductive materials such as carbon or conductive polymers effectively improves the electricalc onductivity and structural integrity.…”
Section: Introductionmentioning
confidence: 99%